Faktor Pendorong dan Penghambat Adopsi Pupuk Organik Cair pada Usahatani Padi di Kabupaten Tana Toraja - Salinding, Herlina; Yunus, Awaluddin; Mahmud, Musdalipa (Lembaga Pengembangan Kinerja Dosen, 2025)
Dependence on chemical fertilizers has caused a decline in soil quality, groundwater contamination, and rising agricultural production costs due to unstable fertilizer prices. In recent years, frequent fertilizer crises have revealed the fragility of reliance on inorganic fertilizers within the national agricultural system. Hence, a transformation toward environmentally friendly and sustainable agriculture is urgently required. This study employed a scoring technique to analyze field observation data, which were narrated based on the written methodology. Respondents’ answers were categorized and classified according to their assumptions or opinions, with scores determined using a Likert scale. The Likert scale measures attitudes, opinions, and perceptions of individuals or groups regarding specific social phenomena. The results showed that key driving factors—such as affordable fertilizer prices, support from agricultural extension workers, and social encouragement from the community—achieved scores above 82%. This finding indicates that external conditions are quite favorable for promoting the use of organic fertilizers. However, major challenges remain, including the limited availability of organic fertilizers in the field and farmers’ long-standing dependency on chemical fertilizers. To address these challenges, it is essential to enhance the market availability of liquid organic fertilizers (POC) through collaboration between producers and farmer groups. Continuous technical assistance should be provided, including demonstration plots that display tangible improvements in rice yields using POC. Furthermore, government support in the form of targeted subsidies or special incentives for farmers transitioning to organic fertilizers is vital, while strengthening the role of farmer groups and agricultural extension workers as catalysts for the adoption of environmentally friendly innovations.